2018
DOI: 10.1111/echo.14105
|View full text |Cite
|
Sign up to set email alerts
|

Giant congenital right atrial epithelioid‐capillary hemangioma with prolonged QT interval: Case report and practical surgical treatment strategy for primary cardiac tumors in children based on 25‐year review of 299 cases

Abstract: Cardiac hemangioma is very rare and accounts for 2%-3% of the primary cardiac tumors. Cardiac epitheloid-capillary hemangioma has not been reported in the pediatric population so far. We report the fatal outcome of a preterm neonate with a huge congenital right atrial epitheloid-capillary hemangioma and elevated serum alpha-fetoprotein, associated with prolonged QT interval. We describe the echocardiographic, computed tomographic (CT) imaging, microscopic and immunohistochemical features of the tumor. Complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Hemangioma (HA) is a benign tumor commonly diagnosed in childhood, specifically in infants with low birth weight as well as premature infants. The etiology and pathogenesis of HAs have been investigated in recent years, but not completely clarified because of its complexity [ 1 , 2 ]. Females are the majority of HA patients, with a female: male rate of approximately 3 : 1, and HA generally occurs about 14 days after birth [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hemangioma (HA) is a benign tumor commonly diagnosed in childhood, specifically in infants with low birth weight as well as premature infants. The etiology and pathogenesis of HAs have been investigated in recent years, but not completely clarified because of its complexity [ 1 , 2 ]. Females are the majority of HA patients, with a female: male rate of approximately 3 : 1, and HA generally occurs about 14 days after birth [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, indications for surgery of cardiac hemangiomas are controversial. Although it is incidentally detected in the majority of cases, most authors advocate surgical removal due to its unpredictable long‐term behavior such as risk of sudden cardiac death, rupture, or embolism 2,3,6,7 . Surgical resection was preferred for our patient as he had presented with documented ventricular tachycardia.…”
Section: Discussionmentioning
confidence: 97%
“…Wang et al 6 presented a case of ventricular arrhythmia consisting bigeminies and premature trigeminies in a patient with endocardial cardiac hemangioma who underwent complete mass excision. Malakan Rad et al 7 reported a congenital right atrial hemangioma associated with prolonged QTc who underwent complete tumor removal. Similarly, our patient presented with documented VT which caused his symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The effusion or mass effect may cause extrinsic compression on the heart and cardiac tamponade. (ii) Cardiac Hemangioma (CH): CH accounts for 2-3% of the primary cardiac tumors with no significant sex predilection (46). The right atrium is the most common location for fetal and neonatal CH, whereas the left ventricle is the most common site for CH in the adulthood (46,47).…”
Section: Cardiac Myxomamentioning
confidence: 99%